2010
DOI: 10.1088/0022-3727/43/49/495204
|View full text |Cite
|
Sign up to set email alerts
|

Heating effects of a non-equilibrium RF corona discharge in atmospheric air

Abstract: Electrical and thermal properties of a single electrode configuration corona discharge generated under radiofrequency high voltage inside an open air gap at pressures above 1 bar is investigated. Time-resolved imaging of the discharge shows a four-step development of the discharge at atmospheric pressure starting by streamers' inception and propagation, evolving in heating waves and stabilizing in a stationary regime until the power supply is switched off. The mean gas temperature reaches about 1700 K in tens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…To evaluate the energy delivery behavior of RF corona discharge, Auzas conducted a detailed measurement of the physical processes of RF corona discharge in the air with pressures up to 2.5 MPa. 84 The results showed that the plasma filaments could propagate several centimeters in length with voltages lower than 20 kV and peak currents around 10 mA, while consumed only tens of milli-Joules energy during a period of a few hundreds of microseconds. It should also be noted that the voltage required was remarkably lower than that of the nanosecond transient plasma.…”
Section: Radio-frequency Ignitionmentioning
confidence: 97%
See 1 more Smart Citation
“…To evaluate the energy delivery behavior of RF corona discharge, Auzas conducted a detailed measurement of the physical processes of RF corona discharge in the air with pressures up to 2.5 MPa. 84 The results showed that the plasma filaments could propagate several centimeters in length with voltages lower than 20 kV and peak currents around 10 mA, while consumed only tens of milli-Joules energy during a period of a few hundreds of microseconds. It should also be noted that the voltage required was remarkably lower than that of the nanosecond transient plasma.…”
Section: Radio-frequency Ignitionmentioning
confidence: 97%
“…The RF energy can be efficiently delivered to the discharge tips only if the system is optimally tuned, including treating the cylinder charge as a part of the electric circuit-a virtual capacitor. According to the publicized results, 51,[81][82][83][84][85][86][87][88][89][90][91][92][93] to date, the leading contenders for RF corona ignition prototyping includes the advanced corona ignition system (ACIS) by Federal Mogul and the Ecoflash corona ignition system by BorgWarner. One of the challenges of RF corona ignition is ensuring the inception of corona discharge while avoiding arc touchdown, especially in high-density conditions when a higher voltage is demanded.…”
Section: Rf Corona Ignitionmentioning
confidence: 99%
“…When the background pressure is increased to 5 atm, the consumption of propane keeps increasing together with other intermediate species; however, the increment does not correlate with the increment in background density. The ion chemistry promoted by the oscillating plasma can be weaker under higher background pressures because of the constrained plasma size and the reduced electron energy [17]. It can also be observed that the NO 2 /NO x ratio under a background pressure of 0.5 MPa is lower than that for a 0.1 MPa background pressure, while the thermal plasma SI case has the smallest effect on NO 2 generation.…”
Section: Effects Of Oscillating Plasma On Propane Oxidizationmentioning
confidence: 98%
“…The diffuse-to-filamentary transition of a nanosecond plasma discharge can be observed for background pressures up to 0.9 MPa [14], and a transition from non-equilibrium plasma to vibrational-rotational equilibrium can also be observed at higher pressures [15]. Engine tests have been conducted to investigate the performance of non-equilibrium plasma, such as nanosecond transient plasma [16] and RF resonant plasma discharges [17]. However, the mechanism of the advantage provided by these technologies under elevated background pressures has not been discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation